Market concentration, supply, quality and prices paid by local authorities in the English care home market - Ferran Espuny Pujol; Ruth Hancock; Morten Hviid; Marcello Morciano; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2019)
We investigate the impact of exogenous local conditions which favour high market concentration on supply, price and quality in local markets for care homes for older people in England. We extend the existing literature in: (i) considering supply capacity as a market outcome alongside price and quality; (ii) taking account of the chain structure of care home supply and differences between the nursing home and residential care home sectors; (iii) introducing a new econometric approach based on reduced form relationships that treats market concentration as a jointly-determined outcome of a complex contested market. We find that areas susceptible to a high degree of market concentration tend to have greatly restricted supply of care home places and (to a lesser extent) a higher average public cost, than areas susceptible to low degree of market concentration. There is no significant evidence that conditions favouring high market concentration affect average care home quality.
Keywords: H75; I11; L22; 330; Care homes; market concentration; price; supply; quality